Lucas Prize in Dynamic Economics (Journal of Political Economy, 2017)
Previous articleNext article FreeLucas Prize in Dynamic EconomicsPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreThe Robert E. Lucas Jr. Prize is awarded biannually for the most interesting paper in the area of Dynamic Economics published in the Journal of Political Economy in the preceding two years. The prize was established in 2016 on the occasion of the celebration of Lucas’s seminal contributions to economics and his Phoenix Prize award.Papers published between August 2014 and June 2016 were considered for the first prize, which has been awarded to Boyan Jovanovic and Peter L. Rousseau for “Extensive and Intensive Investment over the Business Cycle” (Journal of Political Economy 122 [4]: 863–908).This paper empirically shows that extensive investment (i.e., the creation of new firms) rises with aggregate Tobin’s Q, while intensive investment (i.e., the investment of established firms) falls, and it provides a helpful model for understanding this novel fact. A more rapid technological change makes it harder to adapt existing capital. This raises Q and thereby provides new entrants with a comparative advantage. The authors match their model to investment series, including those by venture capitalists, and analyze the consequences for growth, welfare, and stock markets. The paper therefore makes a substantial contribution to understanding the dynamic economics of technological change and investment choices.Fig. 1. Prizewinners Boyan Jovanovic and Peter Rousseau after receiving the Robert E. Lucas Jr. Prize for their paper, “Extensive and Intensive Investment over the Business Cycle.” The prize was awarded at the Journal of Political Economy’s 125th anniversary reception during the 2017 ASSA Annual Meeting in Chicago. From left: Jovanovic, Lucas, and Rousseau.View Large ImageDownload PowerPoint Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 125, Number 1February 2017 Article DOIhttps://doi.org/10.1086/691154 © 2017 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.